Production of High Nutritional Set Yoghurt Fortified with Quinoa Flour and Probiotics - Mabrouk, Ahmed; Effat, Baher (International Journal of Environment, Agriculture and Biotechnology, 2020)
There has been highly attention in supplementation of yoghurt with probiotics and bioactive cereal compounds for enhancing their nutritional and therapeutic functions. So, the propose of this research was planned to develop novel set yoghurt supplemented with quinoa flour and probiotics. Four treatments (control, T1, T2 and T3) of yoghurt were manufactured buffalo’s milk. Control treatment inoculated with Streptococcus thermophiles and Lactobacillus bulgaricus (1:1) without quinoa flour. The other treatments T1, T2 and T3 were manufactured with adding Streptococcus thermophiles and Lactobacillus brevis NRRLB-4527 (1:1), Streptococcus thermophiles and Lactobacillus reuteri NRRLB-14171 (1:1) and Streptococcus thermophiles and Lactobacillus curvatus NBIMCC-3452 (1:1) and quinoa flour at the level of 0.5, 1. and 1.5 % respectively. Yoghurt samples were analyzed when fresh and during cold storage at 5±2o C., the results showed that the pH values took a reverse trend to acidity and gradually decreased by extending storage period. Moreover, fortification of yoghurt with quinoa flour leads to increase in viscosity because of the high starch contents and binding properties of quinoa flour. Furthermore, diacetyl contents were increased but acetaldehyde decreased by extending storage period. The high nutritive value of quinoa flour lead to improve the yoghurt starter and probiotic counts during all refrigeration storage time. The treatment supplemented with 1.5 quinoa flour had the higher counts of Streptococcus thermophiles and Lactobacillus strains. Organoleptic scores were 95, 96, 96 and 94 in treatments control, T1, T2 and T3 respectively. Coliforms were absent in all yoghurt samples either when fresh or during cold storage period. Finally, it can be recommended that yogurt can be fortified with quinoa ﬂour without any defects and showed adequate potential for future dairy application.